THE RELATIONSHIP BETWEEN WEIGHT SELF-STIGMA, EXPERIENTIAL AVOIDANCE, AND BODY MASS INDEX AMONG MALAYSIAN WOMEN WITH OVERWEIGHT - Shubashini Mathialagan; Poh Li Lau (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examined the relationship between weight self-stigma, experiential avoidance, and body mass index among Malaysian women with overweight. A total of 97 Malaysian women with overweight participated in this study by answering a set of questionnaire which consists of items on weight self-stigma, experiential avoidance, and body mass index. Overall, the findings showed that the participants with overweight were grappling with a high level of weight self-stigma. The correlation analysis showed a positive correlation between weight self-stigma and body mass index, experiential avoidance and body mass index and a strong correlation between weight self-stigma and experiential avoidance. The results of the study align with existing Western-based literature, reinforcing the idea that weight self-stigma and experiential avoidance play a crucial role in body mass index. Thus, targeting these two components in weight loss interventions may have the potential to lower body mass index.